ANALISIS KEBUTUHAN MEDIA INOVATIF SCIENCE LOCAL SONG BERUPA KARTUN DIGITAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA DALAM PEMBELAJARAN IPA KELAS 3 SEKOLAH DASAR - Susi Winarni; Anggi Citra Aprilian; Endang Wahyudiana; Anggit Aruwiyantoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning in this modern era has used a lot of technology to help teachers in learning, but it has not been optimal in improving creative thinking skills, because it has not been maximized in the use of digital technology. The learning media used are not yet varied. Teachers have not played a big role in developing learning media so that students' creative thinking skills are still lacking. The purpose of this study was to develop innovative media for Science local songs in the form of digital cartoons to improve the creative thinking skills of grade 3 students of SDN Satriya 03 Tambun. This type of research uses the Rn D method, the development model is in the form of ADDIE, the first stage is Analysis by Borg and Gall. The research method is quantitative descriptive in the form of a questionnaire. The results of the research data obtained an average of 80.4% of students are interested in the use of innovative media, this is the basis and need for the development of innovative media for science local songs in the form of digital cartoons.